2013
DOI: 10.1097/igc.0b013e3182849d53
|View full text |Cite
|
Sign up to set email alerts
|

Radical Surgery With Individualized Postoperative Radiation for Stage IB Cervical Cancer: Oncologic Outcomes and Severe Complications

Abstract: The majority of women with stages IB1-IB2 cervical cancer undergoing radical surgery do not require adjuvant RT, have excellent oncologic outcome, and have low severe complication rates. Nearly one third of our patients required postoperative radiation, with no statistically significant increase in severe complication rate and with similar oncologic outcomes compared with the surgery-only cohort. These data support the continued practice of radical surgery with individualized postoperative radiation for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Of note, the "late complications" including a few cases of short small bowel obstructions and proctitis, which are probably exclusively related to the adjuvant RT were significantly higher. 41 Table 3 summarizes available studies concerning the complication rates reported in the treatment of early cervical cancer. As shown, there are no randomized studies comparing surgery to chemoradiation, and it is difficult to compare the different results because of the variability in grades and types of reported toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the "late complications" including a few cases of short small bowel obstructions and proctitis, which are probably exclusively related to the adjuvant RT were significantly higher. 41 Table 3 summarizes available studies concerning the complication rates reported in the treatment of early cervical cancer. As shown, there are no randomized studies comparing surgery to chemoradiation, and it is difficult to compare the different results because of the variability in grades and types of reported toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Currently patients in LMIC are over-represented in reports of global rates of adverse surgical outcomes[8], with women’s cancers having been long neglected in these settings[9]. Allowing for variations in reporting, overall complication rates for radical hysterectomy are, often from single centres[10], reported at up to 37% [11, 12], and rates of individual complications, e.g. voiding dysfunction, are reported at up to 42%[13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…2, taking considerable heterogeneity into account, there is no evidence of inferior disease-free and overall survival after NSRH in early stage cervical cancer. One can argue that some (single-centre) cohorts of RH do claim higher survival rates [58,59]. However such studies are prone to numerous kinds of bias.…”
Section: Discussionmentioning
confidence: 97%